Advances in 3D-Printed Pediatric Prostheses for Upper Extremity Differences. (3rd August 2016) - Tanaka, Kara S.; Lightdale-Miric, Nina
Abstract : The prohibitive cost of cutting-edge prostheses prevents many children with a limb difference from obtaining them; however, new developments in 3-dimensional (3D) printing have the potential to increase the accessibility, customization, and procurement of such devices. Children with upper limb differences are ideal candidates for currently available 3D-printed devices because they quickly damage and outgrow prostheses, and the low cost of 3D printing makes repairs and upgrades substantially more affordable. Physicians and medical practitioners should become familiar with the possibilities of 3D-printed devices in order to determine the benefits and utility for their patients.